NUMERICAL INTERPRETATION OF 3D GRAVITY WITH TIKHONOV REGULARIZATION APPROACHIMATION - IDRIS NURUL ULUM (NIM 10213078), AHMAD
Gravity method is one of passive geophysical methods by using Earths gravity natural source. In this method, distribution of rocks under the subsurface greatly affects the gravity value in the measurement point, is is caused by variation of any rocks density. In the modeling of subsurface, measurement data must be corrected to get Bouguer anomaly. The corrections are tidal correction, drift, latitude, free air, bourguer and terrain correction around the measurement. In this study, subsurface modeling is constucted by using 3D forward modeling and also inverse modeling. Inverse modeling is contructed by Tikhonov regularization approximation. Regularization parameter used in this study is 1.2 , 0.5 for alpha value, and 1.1 for beta value. Based on these modeling, we get the inversion result is closed to forward modeling.